Perceptions of Bung Karno University Students on National Ideological Resilience in Facing the Threat of Global Capitalism (Oratio Directa, 2023)
Globalization propagates capitalist values that can conflict with Pancasila and Indonesian social philosophy. This qualitative descriptive study examines Bung Karno University students' perceptions of national ideological resilience, threats posed by global capitalism, and possible responses to those threats. Data were collected through literature study and unstructured interviews with students, then examined using audience reception analysis within a critical paradigm. The findings show that students generally understand capitalism at a conceptual level but have difficulty identifying its contemporary manifestations. They associate global capitalism with economic domination, cultural colonization, weakened national identity, and the influence of liberalism and individualism. Although most participants remain optimistic about Pancasila's resilience, they recognize latent threats through sectarianism, digital culture, and proxy-war practices. Strengthening Pancasila-based education, critical ideological literacy, cultural filtering, national self-reliance, and state protection is therefore necessary.
Keywords: Student perceptions; Ideological resilience; Pancasila; Global capitalism; Critical literacy